A Multivariate Analysis of Attitude Towards Teaching - Yaakub, Noran Fauziah (1990)
This study reports the relationship between attitude towards teaching and ethnicity, sex, entry qualification, personality traits and motives for teaching. Thefindings showed that attitude ofIndian trainees was significantly different from that of Malay trainees; but there was no significant difference between attitude of Chinese from that ofMalay trainees. Attitude of male students was not significantly different from that offamale students; and the attitude of SPM students was undifferentiated from that of the STPM students. None of the motive factors was significantly related to attitude. Two personality factors were positively related to attitude, viz., emotional stability and surgency; and another two factors were negatively related to attitude, i.e., paranoid tendency and sophistication.